Groundwater-Driven Evolution of Prebiotic Alkaline Lake Environments - Benjamin M. Tutolo; Robert Perrin; Rachel Lauer; Shane Bossaer; Nicholas J. Tosca; Alec Hutchings; Serhat Sevgen; Michael Nightingale; Daniel Ilg; Eric B. Mott; Thomas Wilson (Life)
Alkaline lakes are thought to have facilitated prebiotic synthesis reactions on the early Earth because their modern analogs accumulate vital chemical feedstocks such as phosphate through the evaporation of dilute groundwaters. Yet, the conditions required for some building block synthesis reactions are distinct from others, and these conditions are generally incompatible with those permissible for nascent cellular function. However, because current scenarios for prebiotic synthesis have not taken account of the physical processes that drive the chemical evolution of alkaline lakes, the potential for the co-occurrence of both prebiotic synthesis and the origins and early evolution of life in prebiotic alkaline lake environments remains poorly constrained. Here, we investigate the dynamics of active, prebiotically relevant alkaline lakes using near-surface geophysics, aqueous geochemistry, and hydrogeologic modeling. Due to their small size, representative range of chemistry, and contrasting evaporation behavior, the investigated, neighboring Last Chance and Goodenough Lakes in British Columbia, Canada offer a uniquely tractable environment for investigating the dynamics of alkaline lake behavior. The results show that the required, extreme phosphate enrichments in alkaline lake waters demand geomorphologically-driven vulnerability to evaporation, while the resultant contrast between evaporated brines and inflowing groundwaters yields Rayleigh–Taylor instabilities and vigorous surface–subsurface cycling and mixing of lake and groundwaters. These results provide a quantitative basis to reconcile conflicting prebiotic requirements of UV light, salinity, metal concentration, and pH in alkaline lake environments. The complex physical and chemical processing inherent to prebiotic alkaline lake environments thus may have not only facilitated prebiotic reaction networks, but also provided habitable environments for the earliest evolution of life.